When Measuring the Same Leads to Different Conclusions~– A Critical Review of Measures Applied to Assess the Degree of Competition in Banking Systems - Toni Richter; Holger Müller; Horst Gischer (Credit and Capital Markets – Kredit und Kapital, 2020)
Economic studies on the degree of competition (DC) in banking systems use various measures which are subsumed under the 1) structure- (e.g. Herfindahl-Hirschman index), 2) conduct- (e.g. Boone indicator) or 3) performance-oriented approach (e.g. Lerner index). Yet, the respective empirical operationalizations of the different DC measures are expected to represent one central construct~– the true DC of a banking system. We review 35 studies covering 15~European banking systems from 1998 to 2007. Contrasting the central construct hypothesis, we find substantial differences in the produced DC measures. Thus, the economic validity of derived conclusions regarding the competition intensity is challenged.
Keywords: E43; E52; E58; L16; 330; Lerner index; Boone indicator; H statistic; CH3; Competition measurement; Central construct hypothesis; Degree of competition (DC); SCP paradigm; European banking system; Banking industry